Comparison of Standard Percutaneous Nephrolithotomy with Mini-Percutaneous Nephrolithotomy for Removal of Renal Stones in Adults (Journal of Renal and Hepatic Disorders, 2021)
Renal stones are the third most common problem affecting about 10% of global population. The management of nephrolithiasis has undergone a complete transformation since the 1980s. Percutaneous nephrolithotomy (PCNL) has established itself an effective and safe technique that delivers high stone-free rate as well as overall shorter treatment time. We aim to compare the outcome of mini-PCNL with standard-PCNL in patients presenting with renal stones. In all, 90 patients fulfilled the selection criteria and randomized into two groups. Group A underwent mini-PCNL whereas Group B underwent standard-PCNL. Pre-operative hemoglobin level was recorded. Duration of procedure as well as drop in hemoglobin level was also recorded. A kidney, ureter, and bladder (KUB) X-ray was performed to confirm the presence of stone and stone-free status. The mean age of patients in mini-PCNL group was 43.11 years and in standard-PCNL group, it was 36.91 years. The mean stone size in patients of mini-PCNL group was 29.53 mm and 31.58 mm in standard-PCNL group. The mean duration of renal stone in mini-PCNL group was 1.91 years and that in standard-PCNL group 1.80 years. The mean operative time in mini-PCNL group was 59.56 min and 61.22 min in standard-PCNL group. The mean fall in hemoglobin in mini-PCNL group was 0.38 g/dL and that in standard-PCNL group 0.51 g/dL. In mini-PCNL group, stone clearance was observed in 42 (93.3%) patients, while in standard-PCNL group, it was observed in 45 (100%) patients. This difference was insignificant (P > 0.05). Mini-PCNL and standard-PCNL have no significant differences in terms of outcome, operative time, and stone clearance, although fall in hemoglobin level was less in mini-PCNL group, which showed less blood loss in this group, thereby making it a more appropriate method for renal stone removal.
Keywords: hemoglobin; mini-percutaneous nephrolithotomy; operative time; renal stone; standard procedure; stone removal